Estimating psychophysiological loads by repeated temperature steps on humans using a state–space model - Miho Iwasaki; Yusuke Morito; Kyosuke Watanabe; Kiyoshi Kuroi; Shota Hori; Yoko Sakata; Kei Mizuno; Kazunobu Okazaki; Yasuyoshi Watanabe (PLoS ONE, 2025)
Humans are exposed to daily temperature differences indoors and outdoors worldwide; however, the associated risks to health and fatigue remain unclear. This study aimed to clarify the psychophysiological loads by repeated short-term temperature differences on Japanese individuals. Herein, 28 healthy individuals were repeatedly moved between two temperature environments, and their psychological/physiological responses to temperature differences in the environment were recorded [T 26-26 (control), T 26-31 (5 °C step), T 26-36 (10 °C step), and T 21-36 (15 °C step)]. We precisely estimated the accumulated effects (load) of repeated temperature steps using a Bayesian state–space model, and distinguished them from the direct effects of environmental changes. The Load to the autonomic nervous system was continuously enhanced (decreased high-frequency of RRI and increased low-frequency/high-frequency of RRI) in the trials with temperature steps, while it was less under the T 21-36 (15 °C step) than under the T 26-36 (10 °C step) condition. These findings could help formulate fatigue management approaches and recommend best practices to minimise adverse health effects related to sudden and uncontrollable environmental temperature steps/changes in everyday scenarios on the public.